Écrire, traduire, publier : la convergence des luttes - Oristelle Bonis; Touriya Fili-Tullon; Souad Labbize; Roula Sadaki (Glad!, 2021)
This contribution constitutes a dialogue between feminist authors, translators and editors. It questions the political and activist dimension of the feminist translation. The article shows how this dimension is realized by creating solidarity and adopting shared struggles beyond linguistic and national boundaries, especially when the texts to be translated deal with traumatic experiences such as rape. The question of the translator’s status and visibility is particularly discussed.